The rationale selection of the modules values for processors in the system of residual classes - Viktor Vasilevich Berezhnoy; Nikolay Nikolaevich Nagornov (Наука. Инновации. Технологии, 2022)
Considered the set systems of modules for 32-bit and 64-bit processors in the residue number system (RNS). Conducted the substantiation of the selection criteria values of the modules: with a minimum of hardware expenses tabular implementation of RNS processor; minimum hardware expenses in the implementation of RNS processor in binary logic; the same type of module channels. Considered various systems of modules in the amount of 25 sets for 32bit and 22 sets for 64-bit processors. Conducted investigations to determine the effectiveness of the use of all sets under consideration systems of modules in terms of each of the criteria. Presents the analysis of the results and selected the best according criteria the systems of modules for each of the processors.